Effectiveness of bevacizumab in the treatment of metastatic colorectal cancer: a systematic review and meta-analysis - Yu Song; Qianqian Mao; Manling Zhou; Cheng-Jiang Liu; Li Kong; Ting Hu (BMC Gastroenterology, 2024)
Abstract Objective To evaluate the benefit of bevacizumab under the comprehensive treatment strategy and its advantages over other drugs, so as to provide reference for the formulation of clinical plans. Methods As of October 1, 2022, the randomized controlled clinical trials of bevacizumab in combination with metastatic colorectal cancer published in PubMed, Cochrane Library and Medline databases were searched. The odds ratio (OR) and its 95% confidence interval (CI) were used to evaluate the short-term disease control effect and long-term survival of the treatment strategy. Results 21 RCTs (6665 patients; 3356 patients in the experimental group and 3309 patients in the control group; average age, 55–75 years) were treated with bevacizumab as the experimental group for metastatic colorectal cancer. BEV has stronger anti-tumor activity than the single treatment scheme (OR = 1.30, 95% CI: 1.11–1.52). And Benefits of the BEV group were 0.73 (0.55, 0.96), 1.26 (0.71, 2.24), 1.63 (0.92, 2.87) and 0.07 (0.02, 0.25) compared with CET, VAN, CED and PAN respectively. The disease control of BEV combined therapy was better (OR = 1.36, 95% CI: 1.04–1.78). The same as compared with cediranib (OR = 1.94, 95% CI: 1.06–3.55). However, the long-term prognosis of BEV, including the overall survival (HRs = 0.98, 95% CI: 0.84–1.15) and progression-free survival (HRs = 1.05,95% CI: 0.97–1.13) were not prolonged. The survival benefits of cetuximab and panitumumab were not reflected. Conclusion The addition of BEV can enhance the anti-tumor ability and disease control, while cetuximab and panitumumab may have stronger ability. However, it did not effectively improve the survival of patients. A more reasonable and effective treatment plan needs more clinical experimental support.